2000
DOI: 10.1034/j.1399-3054.2000.100302.x
|View full text |Cite
|
Sign up to set email alerts
|

Osmoprotectant β‐alanine betaine synthesis in the Plumbaginaceae: S‐adenosyl‐ l‐methionine dependent N‐methylation of β‐alanine to its betaine is via N‐methyl and N,N‐dimethyl β‐alanines

Abstract: Alanine betaine is an osmoprotective compound accumu-donor. Leaf extracts from -alanine betaine accumulators -Armeria maritima, L. latifolium and L. ramosissimum -had lated by most members of the plant family Plumbaginaceae. Leaf and root tissues of Limonium latifolium known to accu-detectable NMT activities while none were found in L. perezii, mulate -alanine betaine readily convert supplied -alanine to a species that does not accumulate -alanine betaine. The -alanine betaine. To identify the intermediates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
3
20
0
1
Order By: Relevance
“…Our previous radiotracer and enzyme measurements showed that ␤-Ala betaine synthesis was specific to ␤-Ala betaine-accumulating members of the Plumbaginaceae (Hanson et al, 1991;Rathinasabapathi et al, 2000). Consistent with this, ␤-Ala NMTase mRNA expression was present in L. latifolium and absent in L. sinuatum (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our previous radiotracer and enzyme measurements showed that ␤-Ala betaine synthesis was specific to ␤-Ala betaine-accumulating members of the Plumbaginaceae (Hanson et al, 1991;Rathinasabapathi et al, 2000). Consistent with this, ␤-Ala NMTase mRNA expression was present in L. latifolium and absent in L. sinuatum (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly, ␤-Ala betaine was distributed among species of the Plumbaginaceae, adapted to a wide range of adverse stress environments including saline and hypoxic conditions (Hanson et al, 1994). Although ␤-Ala betaine accumulation has been intensely studied for its role in osmoprotection (Hanson et al, 1994;Rathinasabapathi et al, 2000Rathinasabapathi et al, , 2001, early work on this compound in marine algae also suggested it to have a cholesterol-reducing effect in animal feeding experiments (Abe and Kaneda, 1973 Article, publication date, and citation information can be found at www.plantphysiol.org/cgi …”
mentioning
confidence: 99%
“…Of these nitrogenous compounds, considerable amounts of both TMA and β-alanine betaine were quantitatively estimated using the developed method (Table 1). Similarly, the concentration of β-alanine betaine in many plants of the family Plumbaginaceae was found in the range of 1 to 147 μg/g DW, which was estimated by either TLC and autoradiography (Rathinasabapathi et al 2000) or 1 H NMR (Baysalfurtana et al 2013). Collectively, the above findings clearly demonstrated the suitability of the developed method for the simultaneous detection and quantification of these analytes in microbial culture and plant samples.…”
Section: Application Of the Methods To Microbial And Plant Samplesmentioning
confidence: 99%
“…Although glycine betaine is extensively accumulated in many plants in response to various environmental stresses, various members of the highly stresstolerant plant family Plumbaginaceae accumulate β-alanine betaine instead of glycine betaine (Hanson et al 1994). β-Alanine betaine synthesis is not controlled by choline availability, because it is derived from β-alanine by threestep methylation (Rathinasabapathi et al 2000). Distinct from glycine betaine synthesis, β-alanine betaine synthesis does not require oxygen, and therefore, it was proposed to be suitable for osmoprotection under saline and hypoxic conditions (Hanson et al 1994;Rathinasabapathi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation